Overqualification at work and risk of hospitalization for psychiatric and somatic diseases among immigrants in Sweden – a prospective register-based study - Brendler-Lindqvist, Maria; Tondel, Martin; Helgesson, Magnus; Nordqvist, Tobias; Svartengren, Magnus (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVES ': 'This study aimed to (i) describe the prevalence of overqualification at work among immigrants in Sweden and (ii) analyze any association between overqualification and the risk of hospitalization for somatic and psychiatric disease among refugees and labor immigrants. ' ' METHODS ': 'We performed a prospective register study in a cohort of 120 339 adults who immigrated to Sweden in 1991–2005 and were employed in 2006. Education-occupation status was defined as the combination of an individual’s highest level of education and their occupation skill level. Individuals were followed from 2007 to 2016 with regard to hospitalization for a psychiatric, cardiovascular, respiratory or musculoskeletal disease or diabetes. Hazard ratios (HR) with 95% confidence intervals (CI) were calculated in a multivariate Cox regression analysis adjusted for age, gender, reason for residence and duration of residence. ' ' RESULTS ': 'The overall prevalence of overqualification among immigrants with an academic education was 39%. Overqualified individuals had an increased risk of hospitalization for any disease (HR 1.33, 95% CI 1.21–1.46) compared to "job-matched with an academic education". However, the risk estimates were lower than that of "job-matched with no academic education" (HR 1.56, 1.46–1.68). The increased risk of hospitalization for a psychiatric disease of overqualified individuals did not differ from that of job-matched with no academic education. ' ' CONCLUSION ': 'Our study showed that being overqualified was associated with poorer health outcomes than job-matched individuals with an academic education. Considering the high prevalence of overqualification in immigrants, this constitutes a concern, for both society and individuals.
Keywords: discrimination; emigration; employment; hospitalization; immigrant; immigration; labor migrant; migrant worker; mismatch; occupation; occupational exposure; occupational health; overqualification; prospective register-based study; psychiatric; refugee; somatic disease; status incongruence; status incongruency; status inconsistency; Sweden; work exposure; working condition